Synthesis Development and Molecular Docking Study of New Azo Chalcone Derivatives - Ibrahim, Myasar Kh.; Mohammed, Shireen R. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
This work is divided into two main parts. The first part involves the synthesis of new azo chalcone compounds through a two-step process. Initially, azo compounds are synthesized by diazotizing 3-nitroaniline, followed by a coupling reaction with 4-hydroxyacetophenone, which has a terminal ketone group. Subsequently, the resulting product undergoes a Claisen–Schmidt condensation reaction with various aromatic aldehyde substrates to produce new α, β-unsaturated ketones, known as azo chalcone compounds. The successful synthesis of these compounds is confirmed using Fourier-transform infrared spectroscopy, ¹HNMR, and ¹³C NMR spectral analyses. The second part of this study explores the theoretical biological activity of the synthesized compounds against severe acute respiratory syndrome coronavirus 2 through molecular docking studies. The results indicate potential antiviral properties for each compound, with compounds B5 and B8 exhibiting the most promising results. These compounds achieved higher docking scores (ΔG −6.235 kcal/mol and −5.832 kcal/mol, respectively) and each formed four hydrogen bonds with the target protein.